Effect of Lactobacillus reuteri Administration on Wrinkle Formation and Type I Procollagen Levels in UVB-Exposed Male Balb/c Mice (Mus musculus) - Ivanna Valentina; Achadiyani Achadiyani; Sunarjati Sudigdo Adi; Ronny Lesmana; Reni Farenia (Molecular and Cellular Biomedical Sciences, 2020)
Background: Chronic Ultraviolet B (UVB) exposure causes oxidative stress that may induce damages to the collagen matrix and thus plays a role in the wrinkle formation. Lactobacillus reuteri is a probiotic that may exerts antioxidant effects, thus helping to reduce damages caused by UVB-induced oxidative stress in the skin.Materials and Methods: Twenty-eight male Balb/c mice were divided equally into control group, UVB radiation only group, oral L. reuteri supplementation only group, and UVB radiation with oral L. reuteri supplementation group. UVB irradiation was given 3 times a week (100 seconds/exposure, within 3 cm distance) for 10 weeks, with a total dose of 166 mJ/cm2. Oral L. reuteri supplementation (0.2 mL, 108 CFU) was provided every morning after meal via orogastric feeding tube for 10 weeks. Wrinkle formation on the dorsal skin of the mice was evaluated in accordance with the Bissett method and type I procollagen levels was evaluated by western blotting.Results: In comparison with the group receiving only UVB irradiation, the group receiving probiotic and UVB irradiation showed significantly lower wrinkle scores (Group 1 vs. Group 3, 2.50±0.55 vs. 1.00±0,00; p<0.05) and significantly higher type I procollagen levels (Group 1 vs. Group 3, 0.88±0.36 vs. 1.92±0.46; p<0.05).Conclusion: Results of the current study showed that L. reuteri supplementation may reduce wrinkle formation and increase type I procollagen production in UVB-exposed dorsal skin of male Balb/c mice.Keywords: Lactobacillus reuteri, type I procollagen, photoaging, wrinkles, ultraviolet B